Musical notations of the orient: Notational Systems of Continental East, South, and Central Asia - Kaufmann, Walter (Bloomington Indiana University Press, 2003)
This book provides a description and preservation of Oriental notational systems, the study of which makes possible a deeper understanding of Eastern art music and demonstrates its character to the student more meaningfully than does the mere presentation of recordings and musical examples written in Western staff notation. The numerous problems arising from styles and techniques which are based upon improvisation and extramusical concepts are also considered.The purposes of this study will have been fulfilled if it serves as a stimulus toward further research in this fascinating, but, alas, quickly vanishing field. The presentation of Eastern notations may also provide some aesthetic pleasure from the study of unusual and often complex systems and symbols. -- from the Preface